2017
DOI: 10.3389/feduc.2017.00065
|View full text |Cite
|
Sign up to set email alerts
|

Affective Profiles in a Massive Open Online Course and Their Relationship with Engagement

Abstract: The importance of affects in learning has been firmly established in face-to-face learning environments, and now researchers are examining the roles of affects in online learning environments, including massive open online courses (MOOCs). The purpose of this research was to identify profiles of common achievement affects (i.e., relief, anxiety, boredom, and guilt) over the duration of one MOOC and examine the differences in academic engagement. Results from the latent profile analysis revealed unique affectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In sum, these findings contribute to the achievement motivation literature in that they unveil psychosocial profiles that arise in an online learning environment (e.g., Tze et al, 2017). The academic experiences of students in online learning settings that involve co-activated cognitive and affective processes have received little attention to date and the addition of online technology can bring further complexity to learning tasks (Daniels & Stupnisky, 2012).…”
Section: Maladaptive Profiles Treatment Interventions and Online Lear...mentioning
confidence: 66%
“…In sum, these findings contribute to the achievement motivation literature in that they unveil psychosocial profiles that arise in an online learning environment (e.g., Tze et al, 2017). The academic experiences of students in online learning settings that involve co-activated cognitive and affective processes have received little attention to date and the addition of online technology can bring further complexity to learning tasks (Daniels & Stupnisky, 2012).…”
Section: Maladaptive Profiles Treatment Interventions and Online Lear...mentioning
confidence: 66%
“…1Tze, Daniels, Buhr, and Le (2017) examined emotion profiles, but profiles were based on repeated measures of the same emotion (not multiple emotions). For this reason, we excluded the study from our literature review.…”
mentioning
confidence: 99%
“…Leony et al [12] infer four kinds of more complex emotions (frustration, confusion, boredom and happiness) in the MOOC platform, based on the four corresponding detection model. The similar taxonomy of learning emotions can be found in [29]- [31]. Some researchers have shown that learner's attention or motivation can be utilized to identify learning engagement in e-learning environment.…”
Section: A Learning Engagementmentioning
confidence: 96%